O espaço paranaense em relatos de viajantes: fronteira, território e ocupação (1870-1900) - Secariolo, Fabiana Marreto (2010)
This study is concerned about the trip stories about the Paraná state during the second half of 19th century. The travellers who compose the documentary corpus are: Nestor Borba, whose story was published in MONUMENTA collection: Stories of a Trip to Guaira and Foz do Iguaçu (1870-1920), with the title Trip to Sete Quedas (Seven Falls) dated of 1876, and the General José Cândido Muricy having a text published in the same collection, with the title Description of a Trip Done From Guarapuava To Foz do Iguassu Colony in November of 1892. It is also analyzed the story of the English engineer Thomas P. Bigg Wither, intitled New Way In Southern Brazil: The Paraná Province: Three years in its forests and fields 1872/1875. These travellers left a rich legacy of information regarding the occupation and exploration of the Paraná state, which allowed us to explore the History of the Paraná in the 19th century in others perspectives. The travellers sayings about the nature, the territory, the borders and the population had constituted a challenge for our interpretation, therefore it was necessary to identify the specificity of each one of them, as well as its cultural references to understand their trip objectives